Case Report: Diffuse Large B-Cell Lymphoma in the Wall of a Thymic Cyst - Agrafiotis, Apostolos C.; Paralikas, Ioannis; Giakoumakis, Kanellos; Moraitis, Sotirios D. (Frontiers in Surgery, 2022)
Thymic cysts are rare lesions (1-5% of all mediastinal masses) and most of the times are incidental findings. The coexistence of a lymphoma and a thymic cyst is rare. In the case reported herein, microscopic foci of a diffuse large B-cell lymphoma were identified in the wall of a resected thymic cyst. This case report adds to the current knowledge about this rare entity and highlights the necessity of early surgical resection of mediastinal cysts over watchful waiting.